Transformative Learning and the Awareness of White Supremacy - BROOKFIELD, Stephen (Phronesis, 2018)
This article describes the development of critical consciousness and the different intellectual traditions that have been influential in framing how this concept is understood. Prime amongst these is analytic philosophy, American pragmatism and Frankfurt School critical theory. Two particular critical moves are analyzed in detail; being willing to subject the assumptions that inform your own, and others’ reasoning and actions to regular scrutiny and being open to alternative perspectives and viewpoints. The author examines the critical theory tradition›s emphasis on deconstructing power and ideological control and uses his own experience of clinical depression to illustrate this. He argues that his depression could only be understood once he was ready to think critically about the ways that the dominant ideology of patriarchy had blocked a critical analysis of his mental state.